2005
DOI: 10.1021/cg050251p
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Interesting Organic Supramolecular Structures in the Solid-State Self-Assembly of Triphenol Adducts

Abstract: Utilization of the interplay of dimensionality (1D, 2D, 3D), orientation of functional groups of the building blocks, influence of rigid/flexible linking groups, and weak interactions provides an interesting route for the creation of novel supramolecular architectures in the crystal lattice. Molecular complexes of triphenol 1 with aza compounds such as pyrazine (pyz), 1,10-phenanthroline (phen), 4,4′-bipyridyl (bpy), trans-1,2-bis(4-pyridyl)ethylene (bpy-ethe), and 1,2-bis(4-pyridyl)ethane (bpy-etha) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Further, it is noted that syn and anti forms of a closely related molecule, 4-[2-(pyridin-4-yl)ethyl]pyridine, are found within the same crystal structure, i.e. in its 1:1 co-crystal with bis(2-hydroxyphenyl)-4-hydroxyphenylmethane [54]. Finally, it is noted that 2 was isolated from a failed co-crystallisation experiment.…”
Section: Discussionmentioning
confidence: 95%
“…Further, it is noted that syn and anti forms of a closely related molecule, 4-[2-(pyridin-4-yl)ethyl]pyridine, are found within the same crystal structure, i.e. in its 1:1 co-crystal with bis(2-hydroxyphenyl)-4-hydroxyphenylmethane [54]. Finally, it is noted that 2 was isolated from a failed co-crystallisation experiment.…”
Section: Discussionmentioning
confidence: 95%
“…However, using ab initio calculations, Vishweshwar and co‐workers found that the acid–amide heterosynthon (b) is more favourable than the acid–acid homosynthon. Others, such as the amide homosynthon (c) and the acid–pyridine (d) heterosynthon are also widely studied in crystal engineering …”
Section: Pharmaceutical Co‐crystalsmentioning
confidence: 99%
“…At the same time, notwithstanding their weak bonding and angular spreading pattern, H-bonds have been approved as directional and predictive intermolecular cohesive forces in molecular packing . Among others, H-bonds as main driving forces in supramolecular assemblies of organic modules featuring functional carboxyl, pyridyl, or a mixture of the two have been comprehensively explored. ,,,,,,, It should also be noted that phenol–amine interplay has been confirmed to be a type of stable and robust driving forces for the exploitation of new solid materials, and the well-defined O–H···N bonds furnished in molecular compounds have been found productive for the generation of a wide variety of supramolecular aggregates . During the course of our investigations in crystal engineering of phenol–amine salts and adducts, we recently discovered that halogenations of bis(4–hydroxyphenyl)sulfone (BPS) would boost the abilities of the functional phenols to form H-bonds in directing molecular assembly and recognition .…”
Section: Introductionmentioning
confidence: 99%